The Role Of English For Banking Subject In Language And English Literature Study Program Faculty Of Language And Arts - Mamentu, A C (Journal of Educational Method and Technology, 2018)
English for Banking subject is offered to the students as an optional subject. This subject is offered to the students in order to anticipate the alumni that will be accepted in the banking related jobs. The aim of this research was to identify the role of English for Banking subject toward students’ readiness in work fields. This research used qulitative method and linear regression analysis with sixteen students as total respondents who are the student of the fourth semester of Language and English Literature Study Program Faculty of Language and Arts UNIMA. The result of this research was the English for Banking has positive influential toward students’ readiness to enter the banking realted job. The subject is suggested to be given in the Language and English Literature Study Program. This shows that the role of English for Banking subject is recommeded as an obligatory subject and not only as an optional subject.Keywords: English for Banking, Role of English